EKSISTENSI TOKOH UTAMA NOVEL 9 MATAHARI DAN KELAYAKANNYA SEBAGAI PEMBELAJARAN SASTRA SMA - Nila Candra; Muhammad Fuad; Edi Suyanto (Universitas Lampung, 2020)
This study aims to describe the existence of the main character and its worthiness as literature learning material for high school students in class XII. The research was conducted through literature study. The results of the study 1) obtained a description of the existence of the main character novel